2015
DOI: 10.1080/13506285.2015.1015663
|View full text |Cite
|
Sign up to set email alerts
|

Visual perceptual learning by operant conditioning training follows rules of contingency

Abstract: Visual perceptual learning (VPL) can occur as a result of a repetitive stimulus-reward pairing in the absence of any task. This suggests that rules that guide Conditioning, such as stimulus-reward contingency (e.g. that stimulus predicts the likelihood of reward), may also guide the formation of VPL. To address this question, we trained subjects with an operant conditioning task in which there were contingencies between the response to one of three orientations and the presence of reward. Results showed that V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
13
1
Order By: Relevance
“…This would be the case for color adaptation (Bompas & O'Regan, 2006), perception in binocular rivalry (Marx & Einhäuser, 2015), or the disambiguation of bistable stimuli (Haijiang, Saunders, Stone, & Backus, 2006). Visual learning-that is, sensitivity changes for critical features of stimuli-may also arise through an automatic process similar to conditioning (Kim, Seitz, & Watanabe, 2015;. Interestingly, Seitz and colleagues showed that visual learning can also occur from unattended, task-irrelevant stimuli if these stimuli are temporally correlated with task-relevant ones (Seitz, Kim, & Watanabe, 2009;Seitz & Watanabe, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This would be the case for color adaptation (Bompas & O'Regan, 2006), perception in binocular rivalry (Marx & Einhäuser, 2015), or the disambiguation of bistable stimuli (Haijiang, Saunders, Stone, & Backus, 2006). Visual learning-that is, sensitivity changes for critical features of stimuli-may also arise through an automatic process similar to conditioning (Kim, Seitz, & Watanabe, 2015;. Interestingly, Seitz and colleagues showed that visual learning can also occur from unattended, task-irrelevant stimuli if these stimuli are temporally correlated with task-relevant ones (Seitz, Kim, & Watanabe, 2009;Seitz & Watanabe, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, because we were simply interested in manipulating arousal state, the likelihood of water delivery was not contingent on a participant's response. This differs from traditional reward paradigms, allowing for purer arousal manipulation (Kim, Seitz, & Watanabe, 2015;O'Doherty, Deichmann, Critchley, & Dolan, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Current models of PL suggest that top-down inputs act to restrict task-dependent plasticity to the appropriate neurons (79)(80)(81)(82)(83) or enhance stimulus signals above some threshold beyond which plasticity mechanisms are operational (58,59). Our hypothesis is consistent with these models but posits that, rather than providing a static modulatory signal, top-down networks change throughout training, thereby contributing to improved ACx sensitivity and PL.…”
Section: Significancementioning
confidence: 99%